Diverse clinical features of symptomatic Meckel’s diverticulum: a multicenter study of 151 consecutive pediatric patients from the Western Balkans - Zlatan Zvizdic (9212371) (2025)
Purpose Symptomatic Meckel’s diverticulum (MD) has various clinical presentations and can be easily misdiagnosed. This multicenter study examines the clinical characteristics, management, and outcomes of patients across five academic pediatric surgery centers in Bosnia & Herzegovina and Serbia. Methods We retrospectively included all pediatric patients (< 18 years) who were surgically and histopathologically confirmed to have symptomatic MD between 2011 and 2020. Demographics, clinical and radiological features, surgical treatment approaches, histopathologic findings, and outcomes were collected and analyzed. Results Among 151 patients (80.1% male), the median age was 6.7 years (IQR 1.5–10.8). Presentations included intestinal obstruction (38.4%), GI bleeding (37.8%), and peritonitis (23.8%); 63.6% had multiple symptoms. A technetium-99 m scan was positive in 80.7% of bleeding cases. Laparotomy was performed in 72.2%, laparoscopy in 23.2%, and conversion in 4.6%. Partial small bowel resection was required in 80.8%, versus diverticulectomy in 19.2% (p < 0.001). Ectopic mucosa was found in 55.6% (gastric 48.3%, pancreatic 2.6%, both 4.6%; p = 0.05), significantly more common in males (p < 0.001). Postoperative complications occurred in 3.2%, with no mortality. Conclusions Symptomatic MD displays highly variable clinical presentations. It is often underdiagnosed preoperatively, particularly without GI bleeding, emphasizing the need for high clinical suspicion and tailored surgical approaches. Other Information Published in: Pediatric Surgery International License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00383-025-06197-2